Too Many Fancy Bottles! In Nepal’s New Power Sector Institutions Electricity Development Decade 2072 - Pun, Santa Bahadur (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Seven years after Prime Minister Dr. BR Bhattarai’s 38 Point programs to Mitigate National Electricity Crisis, the Energy Ministry of Prime Minister KP Sharma (Oli) recently unveiled another program to Eradicate National Electricity Crisis along with a concept paper and work plan on Electricity Development Decade 2072. This article will focus only with the Energy Ministry’s institutional arrangements. The Energy Ministry appears to have come to the grand conclusion that the present state of Bungled power crisis is all due to the Bundled NEA. Hence, the Ministry’s prescription has been to unbundle NEA down to its bare skeleton! There is not a word on the Department of Electricity Development or the Nepal Investment Board – both high caste thread-bearing organizations! It is hoped that a thorough Implementation Completion Report (ICR) will be conducted on three decades of bungled/bundled power sector in Nepal by the World Bank, now that the prodigal son has returned after the 1995 Arun III debacle. Without the findings of that ICR/PCR, the multilaterals should refrain from the itch to unload their one billion US excess baggage on Nepal’s power sector. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 6-10